Complications of Surgical Treatment of Aortic Arch Hypoplasia in Infants - Iaroslav P. Truba; Ivan V. Dziuryi; Roman I. Sekelyk; Oleksandr S. Golovenko; Vasyl V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2021)
Aortic arch surgery in neonatal patients remains problematic despite the constant evolution and improvement of treatment methods. Even after successful correction, complications associated with aortic arch reconstruction are more common in young children. This is especially true for newborns and infants with concomitant complex congenital intracardiac abnormalities. Despite the risk of postoperative complications, the risk of surgical treatment of aortic arch hypoplasia is lower than the cumulative hazards associated with the natural course of this defect. That is why pediatric cardiologists are obliged to constantly monitor the operated patients in order to timely identify and treat complications.The aim. To analyze the complications in the early and remote postoperative periods after the reconstruction of the aortic arch in the neonatal period.Materials and methods. The work is based on a study of 445 patients under 1 year of age, who underwent surgical treatment of aortic arch hypoplasia from 2010 to 2019. The criterion for inclusion in the study group was the presence of isolated hypoplasia of the aortic arch and combination with other defects, which were corrected by two-ventricular repair. The majority of the treated patients were male (284 [63.8% of the total number of patients]). The median age of the patients was 0.7 months (0.3; 2.7). The median body weight of the patients was 3.7 kg (3.25; 4.59).Results. At the hospital stage, 12 patients died, which accounted for 3.1% of the entire cohort of operated patients. Complications occurring at the hospital stage were recorded in 75 (16.8%) patients. In the long term, a complicated course was observed in 72 (16.6%) children. Among them, the most frequent complications were: respiratory failure requiring prolonged mechanical ventilation (36.9%), dilated sternum due to severe heart failure (17.4%), diaphragmatic paresis (8.7%), chylothorax (5.4%). In the long term, 47 (10.5%) patients developed aortic arch restenosis, which required reinterventions. The proportion of patients without reoperations in the follow-up period according to the KaplanMeier analysis was 93.4% after 1 year, 91.2% after 4 years, and 76.5% after 9 years. Residual hypertension requiring medical treatment was reported in 59 (13.2%) patients.Conclusions. Aortic arch hypoplasia is a complex congenital heart disease; its surgical treatment is accompanied by the development of complications both in the early and in the long-term period. The main complications at the hospital stage were respiratory and heart failures which were associated with the presence and correction of concomitant congenital heart defects. The main complication of the follow-up period was reobstruction at the level of the aortic arch. Anatomical correction of reobstruction is safe with both endovascular and surgical treatments.